Evaluation of a class of isatinoids identified from a high-throughput screen of human kinase inhibitors as anti-Sleeping Sickness agents. - Dana M Klug; Rosario Diaz-Gonzalez; Guiomar Pérez-Moreno; Gloria Ceballos-Pérez; Raquel García-Hernández; Veronica Gomez-Pérez; Luis Miguel Ruiz-Pérez; Domingo I Rojas-Barros; Francisco Gamarro; Dolores González-Pacanowska; María S Martínez-Martínez; Pilar Manzano; et al. (PLoS Neglected Tropical Diseases, 2019)
New treatments are needed for neglected tropical diseases (NTDs) such as Human African trypanosomiasis (HAT), Chagas disease, and schistosomiasis. Through a whole organism high-throughput screening campaign, we previously identified 797 human kinase inhibitors that grouped into 59 structural clusters and showed activity against T. brucei, the causative agent of HAT. We herein report the results of further investigation of one of these clusters consisting of substituted isatin derivatives, focusing on establishing structure-activity and -property relationship scope. We also describe their in vitro absorption, distribution, metabolism, and excretion (ADME) properties. For one isatin, NEU-4391, which offered the best activity-property profile, pharmacokinetic parameters were measured in mice.